CROATIAN PEASANT PARTY IN ITALY FROM 1945 TO 1947 (Review of Croatian History, 2021)
The aim of this paper is to present and analyse the hitherto poorly researched activities of the Croatian Peasant Party (CPP) in Italy from June 1945 to mid-1947, based on archival sources of the Yugoslav Secret Service, CPP emigrant media and relevant literature. This is a period that marks the arrival and departure of prominent CPP members from Italy. The paper analyses the mutual relationship of CPP members in the party and their attitude towards other emigrant groups and Croatian refugees. During the observed period, most of the CPP’s pre-war MPs who found themselves in exile resided in Italy, and Italy was then one of the most important party centres of activity.